Optimization of preservation solutions to execute testing on cervical smear sample - Le, Quang Thanh; Pham, Thanh Hai; Nguyen, Quy Thi Cam; Truong, Quoc Phong; Nguyen, Thi Thanh Tam; Pham, Thuy-Hang (Asian Journal of Medical Sciences, 2021)
Background: The common methods to preserve cell for protein analyses are in cold condition or treated with freeze solution and packaging in dry ice for shipping. Solution which can preserve cervical cells at room temperature is preferable and cost consuming for laboratory testing. Aims and Objective: Research and optimized the storage and transport solution for cervical sample which can preserve cells at room temperature for laboratory testing. Materials and Methods: In this study, cervical specimens were collected in 3 different preservation solutions. Storage and transport of samples was at ambient or refrigerated temperature. The effect of preservation solution and temperature was check by cell visualization under microscope and protein measurement. Results: Presence of cells were detected in all three solutions. Among those, HEPES solution can preserve the highest number of cells and at room temperature. Conclusion: HEPES solution appeared suitable to preserve cervical cytology specimens at ambient temperature for further laboratory testing at protein and DNA level.